Primary Cardiac Lymphoma: Importance of Tissue Diagnosis - Lauren Mendelson; Emily Hsu; Hojune Chung; Andrew Hsu (Case Reports in Hematology)
Primary cardiac lymphoma (PCL) is a rare disease entity that can present with severe cardiac and cardioembolic symptoms. We present a 79-year-old male with history of polymalgia rheumatica on chronic prednisone who presented with a two-week history of progressively worsening dyspnea, cough, and a 10 pound weight loss. Transthoracic echocardiogram (TTE) and computed tomography (CT) of the chest showed a large mediastinal mass with invasion of the pericardium. A biopsy of an abdominal soft-tissue mass confirmed the diagnosis of PCL. The patient was treated with two cycles of rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) which was complicated by progressive heart failure requiring substitution of liposomal doxorubicin. The epidemiology, presentation, diagnosis, and treatment options of PCL are discussed.